O conselho municipal de educação de São Roque/SP: a gestão democrática em debate - Silveira, Viviane da Silva (2021)
The emphasis of this research was to analyze the unfolding of the democratic management process through the organization and functioning of the Municipal Council of São Roque/SP (C.M.E-SR) in the perception of the councilors. In a preliminary survey based on research and exploratory studies referring to the term: “Municipal Council of Education”, in theses and dissertations from 2015 to 2018, based on the Capes Thesis Bank Platform, 35 works were found, being 6 doctoral theses and 29 master's dissertations. It is noteworthy that none of the works found refers to the Municipal Council of São Roque/SP. The methodology used was a qualitative approach and the data treatment was performed through content analysis based on the work of Cellard (2014), with regard to the records of the Minutes of the sessions carried out by this managing body, as well as the municipal legislation, and semi-structured interviews with the acting board members. From the study it was possible to notice that in this trajectory of twenty-three years of existence, the C.M.E-SR sought with diligence to get involved in educational issues. However, one of the obstacles that hindered the performance and continuity of referral processes was related to the unjustified absence of directors that resulted in meetings canceled due to insufficient quorum. It is observed from the minutes that the development of the autonomy of the C.M.E-SR was compromised due to the lack of structure for a better functioning, such as: own funds and physical space for the sessions, which were repeatedly claimed. The guiding principle of democratic management still requires more attention and work, as well as openness to participation in decisions concerning municipal education. It is worth mentioning that the councils are collegiate bodies responsible for monitoring the educational actions of the municipality, being constituted in order to represent the voice of society before the government.